PERLINDUNGAN HUKUM BAGI KARYAWAN TERKAIT HAK PESANGON DALAM PERJANJIAN KERJA ATAS PERUSAHAAN YANG DINYATAKAN PAILIT - Susanti, Christina; Yuhelson, Yuhelson; Marni Emmy Mustafa (Journal of Innovation Research and Knowledge, 2025)
Article 95 paragraph (1) of Law No. 6 of 2023 states that in the event that a company is declared bankrupt or liquidated based on the provisions of statutory regulations, wages and other rights that have not been received by workers/laborers are debts whose payment takes priority. However, the fact is that often when a company is declared bankrupt, employees do not receive severance pay rights as stated in the employment agreement. The problem formulation in this research is how to regulate and pay employee severance pay rights related to work agreements with companies that are declared bankrupt? And what is the legal protection for employees who do not receive severance pay rights as stipulated in their employment agreement with a company that has been declared bankrupt? The theories used in this research are the agreement theory according to Mariam Darus Badrulzaman and the legal protection theory according to Satjipto Raharjo. The method used in this research is normative juridical research in the form of library legal materials or secondary data with primary, secondary and tertiary sources of legal materials. The research approach used is statutory, conceptual, analytical and case approaches as well as techniques for collecting legal materials by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The analysis technique for legal materials is carried out using systematic legal interpretation, grammar, and analogy construction. The research results show that the arrangement and payment of employee severance pay rights related to work agreements with companies declared bankrupt are in accordance with the provisions of Article 95 paragraph (1) in conjunction with Article 156 paragraph (2) of the Manpower Law as amended by Law no. 6 of 2023 where the right to employee severance pay has a priority position or is often called preferred creditor which should be received in full before the company loses its authority to manage and transfer its assets by the curator. However, in practice, the right to severance pay for employees in companies declared bankrupt is still waived, this is because all assets are managed by separatist creditors as parties who have the authority to execute material collateral. Legal protection for employees who do not receive severance pay rights as stipulated in work agreements with companies declared bankrupt, namely in the form of repressive legal protection in the form of resolving disputes through litigation. In this case, employees who do not receive severance pay have the right to file a lawsuit against the company that has been declared bankrupt through the Commercial Court and take cassation and judicial review to obtain their rights as stipulated in the employment agreement and the provisions of statutory regulations.